Gujaratis in 17th century Gondar (Ethiopia) - Ramos, Manuel João (2012)
In the late 1940’s, Mr. Armando Aguiar, a Portuguese journalist, toured Africa and Asia sending home reports testifying on the remaining memories of the real or imagined lusophone presence in those parts during the so-called Age of the Discoveries. These reports, dedicated to the architectural and cultural heritage that resulted from centuries' old interactions between the Portuguese overseas' merchant, military and ecclesiastical constellations, were regularly published in the newspaper Diário de Notícias catering to the nationalistic official discourse enhancing the relevance of the past deeds of the Portuguese in the world.